PENGARUH PENGELUARAN PEMERINTAH PADABIDANG PENDIDIKAN DAN BIDANG KESEHATAN TERHADAP KEMISKINAN DI WILAYAH AJATAPPARENG - Hatta, Muhammad (Economos : Jurnal Ekonomi dan Bisnis, 2018)
Fiscal decentralization enters into poverty alleviation strategy in a number of ways. The  study aims to determine the effect of the government expenditure in the sector of education, health, and the dependency level (control variable) directly and indirectly thrugh the quality of human resources and economic growth on the poverty.The study was carried out in the region of Ajatappareng with analysis unit in 5 cities and regencies     in South Sulawesi. The data were collectied thorugh literature review in the form  of secondary of the city and regency government expenditure in education, health, and dependency rate between 2007 and 2011 as well as the quality of human resources, economic grouth and poverty from 2008-2012. The data were analiysed descriptively in quantitative measure. The study indicates that based on functional relationship the quality of human resources has a larger influence than the economic growth on the decrease of poverty. From the view of government expenditure in the educational and health sectors as well as the dependency level, the government larger expenditure in the sector of health provides more influence on the inprovement of the quality of human resources, economic growth, and reduces poverty as compared to expenditure in the sector of education the level of dependency. Both variables only have influence on the quality of human resources. The study is an academic study and limited only to the analysis of the inpact of the expenditure in the sector of healthand education, the level of dependency on the poverty through the quality of human resources, and economic growth.